The COVID-19 Pandemic Seen from a Syndemic Perspective: The LGBTQIA2SP+ Community - Nicola Luigi Bragazzi (MDPI AG, 2021)
An adverse condition or a disease can (either directly or indirectly) interact in a synergistic fashion with other adverse conditions or diseases/maladies, and co-cluster together with them: this fundamental observation is at the basis of the term "syndemic" (a portmanteau for "synergistic epidemic") [...]